Quantifying the energetic contributions of desolvation and π-electron density during translesion DNA synthesis - Motea, Edward A. (Oxford University Press, 2011)
This report examines the molecular mechanism by which high-fidelity DNA polymerases select nucleotides during the replication of an abasic site, a non-instructional DNA lesion. This was accomplished by synthesizing several unique 5-substituted indolyl 2′-deoxyribose triphosphates and defining their kinetic parameters for incorporation opposite an abasic site to interrogate the contributions of π-electron density and solvation energies. In general, the K(d, app) values for hydrophobic non-natural nucleotides are ∼10-fold lower than those measured for isosteric hydrophilic analogs. In addition, k(pol) values for nucleotides that contain less π-electron densities are slower than isosteric analogs possessing higher degrees of π-electron density. The differences in kinetic parameters were used to quantify the energetic contributions of desolvation and π-electron density on nucleotide binding and polymerization rate constant. We demonstrate that analogs lacking hydrogen-bonding capabilities act as chain terminators of translesion DNA replication while analogs with hydrogen bonding functional groups are extended when paired opposite an abasic site. Collectively, the data indicate that the efficiency of nucleotide incorporation opposite an abasic site is controlled by energies associated with nucleobase desolvation and π-electron stacking interactions whereas elongation beyond the lesion is achieved through a combination of base-stacking and hydrogen-bonding interactions.